Cover Feature: Direct Metal‐ and Reagent‐Free Sulfonylation of Phenols with Sodium Sulfinates by Electrosynthesis (Chem. Eur. J. 28/2019). Issue 28 (8th April 2019) - Nikl, Joachim; Lips, Sebastian; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract : Driven by electricity, a powerful and sustainable synthesis of sulfones is possible. This work reports on a direct reagent‐ and metal‐free coupling of phenols with sulfinates using electrosynthesis. This conversion is characterized by its high atomic economy and its simple implementation. The use of sulfinates as a coupling substrate and supporting electrolyte is remarkable, making the usage of additional supporting electrolyte superfluous. More information can be found in the Communication by S. R. Waldvogel et al. onpage 6891 .